The influence of pretrial exposure to community outrage and victim hardship on guilt judgments. Issue 5 (27th May 2016) - Zimmerman, David; Rodriguez, Dario; Bergold, Amanda; Penrod, Steven
ABSTRACT: Although the courts have explicitly expressed concerns about the effects of public sentiment on juries in highly publicized cases, no research has isolated the degree to which jurors' exposure to community outrage and/or prospective social interactions in the community independently influence judgments of guilt. In the current research, jury eligible undergraduates were randomly assigned to conditions in a 2 (negative defendant facts pretrial publicity (PTP): present vs. absent) × 2 (community outrage PTP: present vs. absent) × 2 (anticipated social interaction: present vs. absent) between subjects factorial design. In an online session, participants read articles containing PTP (or not), and two days later they arrived at the lab to serve as mock jurors in a murder case – before the trial they were instructed (or not) that they would interact with people from the community in which the case was taking place. Neither PTP containing extra-evidentiary facts about the defendant nor prospective interaction with the community had main or interactive effects on guilt measures; however, mock jurors rated the defendant as more likely to be guilty when they read information about community outrage and hardships on victims. These findings suggest future avenues of PTP research focusing on community outrage and victim impacts.